S65 Developing a multi-disciplinary thoracic surgery research team improves the recruitment into and quality of clinical trials. (15th November 2016) - Kerr, A; Oswald, N; Kadiri, S; Bancroft, H; Virgilio, E; Webb, J; Bellamy, M; Taylor, J; Bishay, E; Kalkat, M; Steyn, R; Rajesh, P; et al.
Abstract : Objectives: Recruitment into surgical trials historically has been fraught with difficulty. We examine whether developing a multi-disciplinary research team has aided recruitment, data collection, patient retention and so success of clinical trials. In addition we look at effects on the patient experience of the surgical pathway. Methods: We evaluated the development and impact of a specialist thoracic trained research team of nurses and allied health care professionals in a regional thoracic unit from 2009–2015. We assessed the impact on the recruitment into National Institute for Health Research Clinical Research Network (NIHR CRN) thoracic surgery portfolio trials. Patient experience was captured through a survey (n = 30) and research team feedback through interviews (n = 5). During the development, clear leadership and support networks were created, new members were trained by specialist thoracic research nurses to obtain competences in both research and thoracic surgery to enable confident valid informed consent and the collection of robust quality data. Results: Since the development of a specialised thoracic surgery research team in 2010 the number trials have steadily increased and along with number of team members whilst clinical activity remained constant. The number of patient consented into clinical trials increased 7 fold (Table 1 ). From staff interviews a recurring theme was that a clear team structure and a specialist training aided them to be better patient advocate not only in research but in the clinical pathway. Patients universally agreed that involvement of the research team helped reduce their anxiety about their surgery and so enhanced patients experience. Conclusion: The impact of a dedicated research team goes well beyond research but improves clinical care. Having a clear support system and a specialist trained team has increased recruitment and retention into thoracic surgical trials and enhanced the patient's experience of research and the surgical pathway.